THE APPLICATION OF CREATIVE PROBLEM SOLVING METHOD IN TEACHING READING RECOUNT TEXTS TO THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL 2 PALEMBANG - Ana Theriana (Politeknik Negeri Sriwijaya, 2020)
The title of this study was, “The Application of Creative Problem Solving Method in Teaching Reading Recount Texts to the Tenth Grade Students of Senior High School 2 Palembang”. The purpose of this study was to find out whether there was significance difference or not between the students who were taught in Application of Creative Problem Solving Method in Reading Recount Texts to the Tenth Grade Students of Senior High School 2 Palembang and those who were not. Nonequivalent control group design of quasi-experimental design was applied in this study. Based on the result of this study, the creative problem solving method could improve students’ achievement in reading recount text. It was gained from the students’ post-test scores in the experimental group which were higher than the control group where the average of students’ posttest in experimental group was 78.19 and post test in control group was 68.68. From the calculation of the data, it was found out that score of t-obtained was 4.099 and score of t-table was 1.994. With significance level (0.05) for two tailed. It meant that t-obtained was higher than t-table, 4.099 > 1.994. Since t obtained was higher than t-table, the Null hypothesis (Ho) was rejected and Alternative hypothesis (Ha) was accepted. It could be concluded that there was a significant difference between the students taught in Application of Creative Problem Solving Method in Reading Recount Texts to the Tenth Grade Students of Senior High School 2 Palembang and those who were not.